Forensic Psychological Examination of Information Materials in the System of Scientific Knowledge - Tat’yana N. Sekerazh (Теория и практика судебной экспертизы)
In the article, the author defines the place which a new direction of forensic psychological examination – the study of information materials – occupies in the system of forensic science and the general classification of forensic examinations. Comparison of the object, subject, tasks, and methods of the traditional forensic psychological analysis conducted on living persons and post-mortem examinations, and forensic psychological examination of information materials allows to consider them as generic within the subclass “Forensic psychological examination” in the system of the class “Forensic medical and psychological examinations”. The author maps out the interdisciplinary connections of the psychological examination of information materials and its interaction with various branches of psychological science. It is shown that the systematization of the internal and external scientific relations of the new kind (type) of forensic analysis allows a more comprehensive description of the content of a forensic expert’s specialized knowledge obtained during both diploma and postgraduate training and expert practice.